Birds of Malaysia: covering Peninsular Malaysia, Malaysian Borneo & Singapore - Chong, Leong Puan; Davison, Geoffrey; Kim, Chye Lim (Lynx Edicions, 2020)
The country of Malaysia comprises two halves separated by the South China Sea, the Peninsula and East Malaysia, the latter made up of the states of Sabah and Sarawak. In addition, this new guide also fully covers the independent Republic of Singapore, off the southern tip of the Malay Peninsula. Most of the many Bornean endemic birds can be found in East Malaysia, including a dazzling array of pheasants, frogmouths, trogons, pittas, thrushes, and two of the most recently described birds in the world, Spectacled Flowerpecker and Cream-eyed Bulbul, both named to science only in 2019. The peninsula boasts some of the best lowland forest reserves in the Sundaic region, including the world-renowned Taman Negara National Park, as well as a variety of highland endemics at famous hill station birding sites like Fraser’s Hill. Three monospecific and particularly striking families, the Pityriasidae (Bornean Bristlehead), Platylophidae (Crested Jay) and Eupetidae (Rail-babbler), are best searched for in Malaysia, making the country an essential destination for ‘family collectors’. In addition to taking account of all the most recent taxonomic developments at the time of writing, the authors also highlight some potentially forthcoming changes. Complementing the plates, maps and species texts, the book’s introduction describes the region’s landscapes, habitats and climate, and provides tips on birding in Malaysia and Singapore, along with brief details of 50 of the best sites to visit. Whether you are planning a comprehensive birding tour of the Peninsula and/or northern Borneo, or only to ‘escape’ for a few days while in Singapore, this new guide covers it all.